2017
DOI: 10.1017/s0022215116009221
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of voice outcomes and complication rates in patients undergoing injection laryngoplasty performed under local versus general anaesthesia: an Adelaide voice specialist's experience

Abstract: Injection laryngoplasties performed under general anaesthesia and local anaesthesia offer similar voice outcomes, with comparable complication rates. Hence, development of a management algorithm for injection laryngoplasties performed under local anaesthesia is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…In fact, multiple authors have reported on the safety and efficacy of in-office techniques used as alternatives to examination and biopsy under anaesthesia 3 6 . Lippert et al .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiple authors have reported on the safety and efficacy of in-office techniques used as alternatives to examination and biopsy under anaesthesia 3 6 . Lippert et al .…”
Section: Discussionmentioning
confidence: 99%
“…, 2 Current evidence indicates comparable clinical outcomes and complication rates for procedures such as injection laryngoplasty and oesophagoscopy that are performed in-office under LA and in the operating theatre using GA 1 5 A study recently conducted in Australia showed similar voice outcomes with low complication rates for injection laryngoplasty performed under both anaesthetic modalities 6 . Despite comparable outcomes, major advantages of injection laryngoplasty under LA are the ability to titrate the amount of injection material and procedural precision when injecting into the vocal fold, as the patient is able to phonate during the procedure 7 .…”
Section: Introductionmentioning
confidence: 98%
“…In his report of 34 patients, there was significant improvement in the perceptual parameters, acoustic measures, mucosal wave, and glottic closure post-operatively. Chandran et al 20 reported the Australian experience of 34 injections performed under either local or general anesthesia with improvement in the VHI-10, all perceptual parameters except asthenia, and a less than 10% complication rate. Barbu et al 21 in their investigation on the feasibility of bed side injection laryngoplasty using the transoral approach in the immediate post-operative period have reported advancement in oral intake in 70 percent of patients, thus supporting the importance of early intervention.…”
Section: Discussionmentioning
confidence: 99%